Using the Acropora digitifera genome to understand coral responses to environmental change - Shinzato, Chuya; Shoguchi, Eiichi; Kawashima, Takeshi; Hamada, Mayuko; Hisata, Kanako; Tanaka, Makiko; Fujie, Manabu; Fujiwara, Mayuki; Koyanagi, Ryo; Ikuta, Tetsuro; Fujiyama, Asao; Miller, David J.; et al. (Nature (London), 2011)
A coral reef genome Coral reefs are among the most biologically diverse ecosystems on the planet and are of great economic importance. They are under threat because the scleractinian corals at their core are susceptible to ocean acidification and rising seawater temperatures. The genome of the reef-building coral Acropora digitifera has been analysed with a view to understanding the molecular basis of symbiosis and responses to environmental change. The coral seems to have lost a key enzyme of cysteine biosynthesis, so may be dependent on its symbionts for this amino acid. It contains several genes with roles in protection from ultraviolet light that may have been acquired by horizontal transfer from prokaryotic organisms. The coral's innate immunity repertoire is more complex than that of the solitary sea anemone, suggesting that some of these genes are involved in symbiosis or coloniality. Despite the enormous ecological and economic importance of coral reefs, the keystone organisms in their establishment, the scleractinian corals, increasingly face a range of anthropogenic challenges including ocean acidification and seawater temperature rise 1 , 2 , 3 , 4 . To understand better the molecular mechanisms underlying coral biology, here we decoded the approximately 420-megabase genome of Acropora digitifera using next-generation sequencing technology. This genome contains approximately 23,700 gene models. Molecular phylogenetics indicate that the coral and the sea anemone Nematostella vectensis diverged approximately 500 million years ago, considerably earlier than the time over which modern corals are represented in the fossil record (∼240 million years ago) 5 . Despite the long evolutionary history of the endosymbiosis, no evidence was found for horizontal transfer of genes from symbiont to host. However, unlike several other corals, Acropora seems to lack an enzyme essential for cysteine biosynthesis, implying dependency of this coral on its symbionts for this amino acid. Corals inhabit environments where they are frequently exposed to high levels of solar radiation, and analysis of the Acropora genome data indicates that the coral host can independently carry out de novo synthesis of mycosporine-like amino acids, which are potent ultraviolet-protective compounds. In addition, the coral innate immunity repertoire is notably more complex than that of the sea anemone, indicating that some of these genes may have roles in symbiosis or coloniality. A number of genes with putative roles in calcification were identified, and several of these are restricted to corals. The coral genome provides a platform for understanding the molecular basis of symbiosis and responses to environmental changes.